2018
DOI: 10.1136/oemed-2017-104944
|View full text |Cite
|
Sign up to set email alerts
|

Identifying occupational carcinogens: an update from the IARC Monographs

Abstract: The recognition of occupational carcinogens is important for primary prevention, compensation and surveillance of exposed workers, as well as identifying causes of cancer in the general population. This study updates previously published lists of known occupational carcinogens while providing additional information on cancer type, exposure scenarios and routes, and discussing trends in the identification of carcinogens over time. Data were extracted from International Agency for Research on Cancer (IARC) Monog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
157
0
23

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 217 publications
(180 citation statements)
references
References 21 publications
0
157
0
23
Order By: Relevance
“…Siemiatycki et al 5 indicated that 16 more had been identified by 2004,5 and an additional 24 have been added since 2004 1. This pattern documents the success of epidemiological investigations in identifying cancer hazards in the workplace and may even indicate a quickening of the pace of discovery 1.…”
mentioning
confidence: 95%
See 4 more Smart Citations
“…Siemiatycki et al 5 indicated that 16 more had been identified by 2004,5 and an additional 24 have been added since 2004 1. This pattern documents the success of epidemiological investigations in identifying cancer hazards in the workplace and may even indicate a quickening of the pace of discovery 1.…”
mentioning
confidence: 95%
“…Loomis et al 1 use carcinogenicity evaluations completed by the International Agency for Research on Cancer (IARC) to characterise occupational exposures by tumour type, exposure scenarios and changing patterns of identification over time. Using the IARC classifications of occupational cancers, Marant Micallef et al 2 reviewed the literature to assemble the best-available relative risk estimates for each carcinogen–cancer site pair.…”
mentioning
confidence: 99%
See 3 more Smart Citations